Participatory Community Empowerment for Conflict Management and Peacebuilding in Multicultural Island Settings - Jefry Ernest Marthin Leiwakabessy; Fransina Matakena; Simona Christina Henderika Litaay; Axl Picauly; Tiara Polnaya; Puput Safiteri (CV. TOTUS TUUS, 2025)
Maluku Province, Indonesia, is an archipelago characterized by its vibrant cultural, ethnic, and social diversity, but also by recurrent conflicts linked to land, identity, and historical grievances. This study reports on a community service initiative in Negeri Laha, Ambon, designed to enhance local capacities for conflict management and resolution. Employing participatory action research, the program delivered a series of workshops and interactive dialogues focused on the causes, dynamics, and solutions for conflict, with special attention to land disputes involving the Indonesian Air Force and local residents. Thirty participants, including youth, women, traditional, and religious leaders, engaged in case simulations, collaborative reflection, and practical training in negotiation and mediation. The results indicate a significant increase in participants’ understanding of conflict sources, practical confidence in resolution strategies, and motivation to continue peacebuilding efforts. Key barriers identified include deep-seated mistrust, external influences, and limited institutional support for ongoing reconciliation. The initiative’s emphasis on inclusive engagement, local leadership, and culturally relevant dialogue aligns with best practices in global peacebuilding literature and demonstrates the value of university-community collaboration. This model offers promising implications for other multicultural and conflict-prone areas, supporting both immediate dispute resolution and the development of sustainable local peace infrastructures. Future efforts should prioritize sustained capacity-building, regular dialogue forums, and integrated support from government and civil society to maintain long-term social harmony and resilience.